Performance optimization of cesium silver bismuth bromide-based perovskite solar cell using CZTS buffer layer: A device modeling approach - Aqsa Islam; Hafeez Anwar; Yasir Jamil; Muhammad Shahid (Results in Engineering)
Cesium silver bismuth bromide (Cs2AgBiBr6) has emerged as a highly promising material for photovoltaic applications due to its lead-free composition and favorable optoelectronic properties. This study investigated the performance of perovskite solar cells (PSCs) with a device structure of Metal/Cu2O/CZTS/Cs2AgBiBr6/TiO2/TCO/Glass using Cs2AgBiBr6 as the perovskite layer. The interface engineering at the perovskite/Cu2O interface by the introduction of CZTS (Cu2ZnSnS4) as a buffer layer significantly enhanced the PSC performance due to improved energy band alignment. Without a buffer layer, the device achieved an efficiency of 11.65% with JSC, VOC and FF of 11.86 mA/cm2, 1.11 V and 88.86%, respectively. The addition of a buffer layer substantially increased these parameters resulting in an efficiency of 23.91%, VOC of 1.15 V, JSC of 23.35 mA/cm2 and FF of 89.20%. Further optimization of device parameters using the SCAPS-1D, including the thickness of the buffer layer, electron affinity of buffer layer and hole transport layer (HTL), was performed. In addition to this, the effect of the doping density of HTL, electron transport layer (ETL), and buffer layer was also studied. This optimization led to a remarkable increase in efficiency of 37.02%. The research highlights the significant potential of buffer layer-based PSCs and provides valuable insights for their further development.